2019
DOI: 10.21638/11701/spbu01.2019.402
|View full text |Cite
|
Sign up to set email alerts
|

On Leonov’s method for computing the linearization of the transverse dynamics and analysis of Zhukovsky stability

Abstract: Статья посвящена обсуждению одного из результатов Г. А. Леонова по исследованию устойчивости по Жуковскому решения нелинейного дифференциального уравнения при помощи оригинального метода вывода линеаризации трансверсальной динамики. Показано, что предложенный Леоновым метод может быть эффектно использован как в решении задачи синтеза обратной связи для управления движением механической системы, так и в анализе поведения замкнутой системы. Ключевые слова: подвижное сечение Пуанкаре, устойчивость по Жуковскому, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The problem of asymptotic orbital stabilization of γ τ can be solved using a stabilizing feedback control law for the trivial solutionξ = 0 of (4) and exploiting the fact that under certain conditions, see e.g. [11],…”
Section: A Problem Formulationmentioning
confidence: 99%
See 2 more Smart Citations
“…The problem of asymptotic orbital stabilization of γ τ can be solved using a stabilizing feedback control law for the trivial solutionξ = 0 of (4) and exploiting the fact that under certain conditions, see e.g. [11],…”
Section: A Problem Formulationmentioning
confidence: 99%
“…It can be shown that asymptotic stabilization of the trivial solution of (13) can be used to design an asymptotically orbitally stabilizing controller for (15), see e.g. [14], [15], [5], [7], [11]. Notice that matrices A τ , B τ are smooth periodic functions.…”
Section: Orbital Stabilizationmentioning
confidence: 99%
See 1 more Smart Citation